African American prostate cancer survivorship: Exploring the role of social support in quality of life after radical prostatectomy. Issue 4 (4th July 2017) - Imm, Kellie R.; Williams, Faustine; Housten, Ashley J.; Colditz, Graham A.; Drake, Bettina F.; Gilbert, Keon L.; Yang, Lin
ABSTRACT: Purpose : The aim of this study was to explore the African American prostate cancer survivorship experience following radical prostatectomy and factors contributing to quality of life during survival. Design : African American men who were part of a larger prostate cancer cohort were invited to participate in a focus group. Eighteen open-ended questions were designed by the study team and an experienced moderator to elicit participants' survivorship experiences. Results : Twelve men consented to participate in the study. Emergent themes included views of prostate cancer in the African American community, perceptions of normalcy, emotional side effects following radical prostatectomy, and social support involvement and impact during recovery. Conclusions : Previous findings suggest that African American men may experience more distress than Caucasian men when facing typical prostate cancer side effects. Traditional masculine role norms and negative perceptions of "disease disclosure" in the African American community could be contributing to the distress reported by some in this study. Strengthening social support systems by promoting more prosocial coping and help-seeking behaviors early in the survivorship journey may help bypass the detrimental health effects associated with masculine role identification, resulting in improved quality of life throughout the lengthy survival period anticipated for these men.